ANALISIS PEMBELAJARAN IPS DARING PADA PANDEMI COVID-19 DI SEKOLAH DASAR - Erliska Pranandari (Dharmas Education Journal (DE_Journal), 2022)
This study aims to analyze the results of online social studies learning learning in the Covid-19 pandemic. The subjects of this study were teachers and students at SDN 008 Rambah Samo in the 2020/2021 academic year. This study uses a qualitative research method with a case study approach which includes the stages of observation, interviews, and data analysis. From the research results, the online social studies learning process is carried out using social media, namely whatsapp. Whatsapp is considered simpler and more practical to use for the learning process. However, online social studies learning also has a negative impact and obstacles in the implementation of learning which are directly felt by teachers, students and guardians of students. The negative impact for teachers is also very large, namely the limitations of space and time in the delivery of material, reduced intensity of reciprocal interaction between teachers and students as it should be when face to face. Therefore, as a teacher, they must have interesting innovations in using the method of delivering material for the learning process.